Identification of a rare compound heterozygous hemoglobin variant β0-thal [β17(A14) Lys>Stop, HBB: c.52A>T] and Hb J-Lome [β59(E3) Lys>Asn, HBB: c.180G>C]. Issue 1 (31st December 2022) - Chen, Zixin; Shao, Limei; Jiang, Mingfeng; Ma, Run; Ping, Hongfen; Wang, Zuo; Ba, Xuejiao; Ma, Bingjie; Zhou, Tao
ABSTRACT: Background: HbA1c is the validated biomarker for glycemic management in diabetic individuals. Here, we report a compound heterozygote for β 0 -thal and Hb J-Lomeand evaluate its effect on HbA1c measurements. Methods: A 51-year-old female was suspected of harboring a hemoglobin variant following no value of HbA1c levelby Arkray HA-8180 V (48s HbA1c mode), abnormal hematological data, and abnormalhemoglobin analysison capillary electrophoresis (Capillarys 2 Flex Piercing, Hb program). Sanger sequencing of the α and β genes was subsequently performed on the proband.HbA1c was reanalyzed using D10 (Bio-Rad), Capillarys 2 Flex Piercing (Sebia), and Roche Cobas c501 (Roche Diagnostics). Results: Sanger sequencing identified a compound heterozygote for β 0 -thal [β17(A14) Lys > Stop, HBB: c.52A > T] and Hb J-Lome [β59(E3) Lys > Asn, HBB: c.180G > C].HbA1c values ⁣⁣determinedby D10, Capillarys 2 Flex Piercing (HbA1c program), and Roche Cobas c501were 2.3%, no HbA1c value, and 5.1 (32 mmol/mol), respectively. During pedigree analysis, the son of the proband was found to have normal blood glucose (5.55 mmol/L), decreased HbA1c (3.6%, 16 mmol/mol)by Arkray HA-8180 V (48s HbA1c mode), an abnormal band on the electrophoretogram of Capillarys2 (Hb program), and the Hb J-Lome mutation in the β globin gene.Subsequently, HbA1c values ⁣⁣determinedby D10, Capillarys 2 Flex Piercing (HbA1c program), and Roche Cobas c501 were4.0% (20 mmol/mol), no HbA1c value, and 5.0 (31 mmol/mol), respectively. Conclusion: Atypically low HbA1c levels or a discrepancy between blood glucose and HbA1c levels should raise concerns about hemoglobin variations.